Promoting pneumonia preventive measures among children under one year old at Kasungu district hospital. - Kumwenda, Maria (Kamuzu University of Health Sciences, 2022)
Kasungu District Hospital is one of the seven districts reporting high rates of pneumonia in children under five years old in Malawi. It is against this background that the study is undertaken to promote uptake of pneumonia preventive measures among children. A descriptive qualitative study will be used targeting mothers of children less than one year admitted with pneumonia. A purposive sampling will be used and 15 participants will be interviewed using a structured questionnaire. All ethical consideration will be taken care of by the researcher. Data will be analyzed manually using thematic and content analysis and will be presented in narrative form. Dissemination of results will be done through a written report to Kasungu District Health Office and Kamuzu College of Nursing Library. This will later be communicated to mothers in paediatric ward and under five clinics. The study will help to prevent pneumonia in children and hence reduce child mortality rate in Malawi.